MURABAHA FINANCING OF THE INDONESIAN ISLAMIC BANKS UNDER AN ISLAMIC ECONOMIC LAW AND THE FATWA DSN MUI - Bismi Khalidin; Armiadi Musa; Andri Kiawan (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2023)
This study conducts a thorough analysis of the practice of Murabaha financing within Islamic banks, contextualized within the framework of Islamic economic law and the influential Fatwa issued by the Indonesian Ulema Council (Majelis Ulama Indonesia - MUI). Murabaha, a fundamental mode of Islamic finance, involves a cost-plus-profit arrangement that adheres to Shariah principles. This analysis delves into the core principles of Islamic economic law, which include fairness, transparency, and adherence to ethical financial conduct, and investigates how these principles are manifested in Murabaha transactions. Central to this examination is the Fatwa issued by the MUI, which serves as a guiding regulatory framework for Murabaha financing. This Fatwa provides essential guidelines to ensure the compatibility of Murabaha transactions with Shariah principles and ethical practices. By exploring the origins, key features, and benefits of Murabaha financing as guided by the Fatwa DSN MUI, this study highlights the intricate dynamics through which Islamic banks in Indonesia operationalize this financing mode while upholding the tenets of Islamic economic law. The research results show that the implementation of murabahah financing carried out by sharia banks in Indonesia is not fully in accordance with Sharia Economic Law and the Fatwa DSN MUI. Murabahah financing is basically a form of buying and selling with a profit margin system, but the practice is almost like a form of credit with an interest system as practiced by conventional banks. Abstrak: Penelitian ini bertujuan menganalisis praktik pembiayaan Murabahah pada perbankan syariah dalam Prespektif Hukum Ekonomi Islam dan Fatwa DSN Majelis Ulama Indonesia (MUI). Murabahah adalah sebuah model transaksi dalam keuangan Islam dengan sistem profit margin yang sesuai dengan prinsip-prinsip syariah. Analisis ini menggali prinsip-prinsip inti hukum ekonomi Islam, yang mencakup keadilan dan kepatuhan terhadap perilaku keuangan, dan menyelidiki bagaimana prinsip-prinsip ini diwujudkan dalam transaksi Murabahah. Inti dari penelitian ini adalah Fatwa yang dikeluarkan oleh MUI, yang berfungsi sebagai pedoman kerangka peraturan/ketentuam untuk pembiayaan Murabahah. Fatwa ini memberikan pedoman penting untuk memastikan kesesuaian transaksi Murabahah dengan prinsip-prinsip syariah. Hasil penelitian menunjukkan bahwa implementasi pembiayaan murabahah yang dilakukan oleh bank-bank syariah di Indonesia tidak sepenuhnya sesuai dengan Hukum Ekonomi Syariah dan Fatwa DSN MUI. Pembiayaan murabahah pada dasarnya adalah suatu bentuk jual beli dengan sistem margin keuntungan, tetapi praktik yang dilakukan hampir seperti bentuk kredit dengan sistem bunga seperti yang dipraktikan oleh bank-bank konvensional. Kata Kunci: Pembiayaan Murabahah, Bank Syariah, Hukum Ekonomi Syariah dan Fatwa DSN MUI